PENDUGAAN PARAMETER GENETIK JUMLAH BUNGA DAN BENIH HASIL BUAH DAN BENIH BEBERAPA GENOTIPE CABAI (CAPSICUM ANNUUM L.) TETUA DAN HASIL PERSILANGAN DIALEL DI KEBUN PERCOBAAN CIPANAS JAWA BARAT - Ekowahyuni, Luluk Prihastuti; Yenisbar, - (E-Journal Widya Kesehatan dan Lingkungan, 2018)
Peppers (Capsicum annum L.) is an important horticultural product commercially cultivated in the tropics, including Indonesia, and potentially very strategic in increasing farmers' income as demand and utilization of chili continues to increase, along with the increasing population and consumption per capita . This study aims to determine the value estimate genetic parameters, namely: (1) heterosis for the number of seeds. the amount of fruit and number of flowers in bloom, (2) and combining particular value (DGK) the amount of fruit and flowers to determine the amount of hybrid seed in the future. This research was conducted at the experimental farm Cipanas West Java. The method used is a cross diallel with the study design randomized block design with three replications. Results from this study are the estimation of the value of genetic parameters for the value: (1) heterosis hybrids that have the highest value of heterosis for the number of seeds is IPBC 15x20, for the amount of fruit is IPBC 15x20, for the number of blooms is IPBC 2x20, (2) Hybrid that has a value of specific combining ability (SCA) for the highest number of fruit is IPBC2x20, for DGK to the number of blooms is IPBC 2x20. This shows that the planting in the garden Cipanas and agro-climatic conditions unfavorable already there is a collection of superior parental genotypes that IPB C15, C20 IPB, IPB C2.